Metaphor at work: a study of metaphors used by European architects when talking about their projects - Paloma Úbeda Mansilla (Ibérica, 2003)
There is a significant amount of research in the field of metaphor, but not so much in the use of this resource by a particular socio-professional group, and very few works have included the views and opinions of the correspondent users -this paper moves one step forward in that direction. Based on a major pragmatics research on metaphors in the field of architecture aimed at the design of a course of English for students of Architecture in Spain, the following paper analyses the results of a survey to find out how English architects refer to city and building as two basic categories in their working environment. The main objective is to find out how important the use of metaphors for architects is in order to communicate ideas and concepts about their projects. The conclusions are based on an empirical study carried out in five macro-architectural practices1 in London City through the use of a focused cognitive questionnaire handed out in situ. The analysis shows that unconscious and continuous use of metaphors when referring to the basic categories of building and city constitute a powerful basis for communication at work, transmitting concepts and ideas according to a common cognitive map. Finally, the importance of contextual background and its implications in the use of technical English among European architects is pointed out.